HETDEX Public Source Catalog 1—Stacking 50,000 Lyman Alpha Emitters - Dustin Davis; Karl Gebhardt; Erin Mentuch Cooper; William P. Bowman; Barbara Garcia Castanheira; John Chisholm; Robin Ciardullo; Maximilian Fabricius; Daniel J. Farrow; Steven L. Finkelstein; Caryl Gronwall; Eric Gawiser; et al. (The Astrophysical Journal, 2023)
We describe the ensemble properties of the 1.9 < z < 3.5 Lyman alpha emitters (LAEs) found in the HETDEX survey’s first public data release, HETDEX Public Source Catalog 1. Stacking the low-resolution ( R ∼ 800) spectra greatly increases the signal-to-noise ratio (S/N), revealing spectral features otherwise hidden by noise, and we show that the stacked spectrum is representative of an average member of the set. The flux-limited, Ly α S/N restricted stack of 50,000 HETDEX LAEs shows the ensemble biweight average z ∼ 2.6 LAE to be a blue (UV continuum slope ∼ −2.4 and E(B – V) < 0.1), moderately bright ( M _UV ∼ −19.7) star-forming galaxy with strong Ly α emission (log L _Ly _α ∼ 42.8 and W _λ (Ly α ) ∼ 114 Å), and potentially significant leakage of ionizing radiation. The rest-frame UV light is dominated by a young, metal-poor stellar population with an average age of 5–15 Myr and metallicity of 0.2–0.3 Z _⊙ .